2019
DOI: 10.3390/nu11061348
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine, but not Branched-Chain Amino Acids, Restores Intestinal Barrier Function during Activity-Based Anorexia

Abstract: Background: During activity-based anorexia (ABA) in mice, enhanced paracellular permeability and reduced protein synthesis have been shown in the colon while the gut–brain axis has received increasing attention in the regulation of intestinal and mood disorders that frequently occur during anorexia nervosa, a severe eating disorder for which there is no specific treatment. In the present study, we assessed the effects of oral glutamine (Gln) or branched-chain amino acids (BCAA) supplementation during ABA to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…Intestinal barrier alterations in ABA were reported by Jesus et al Colonic histology showed decreased thickness of the muscularis layer in ABA and colonic permeability was increased in ABA compared to control animals, while jejunal permeability was not affected (Jesus et al, 2014 ). ABA mice exhibited increased paracellular permeability and reduced protein synthesis in the colonic mucosa (L'Huillier et al, 2019 ). Oral glutamine supplementation restored colonic paracellular permeability and protein synthesis and increased the mucin-2 mRNA level without affecting body weight (L'Huillier et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal barrier alterations in ABA were reported by Jesus et al Colonic histology showed decreased thickness of the muscularis layer in ABA and colonic permeability was increased in ABA compared to control animals, while jejunal permeability was not affected (Jesus et al, 2014 ). ABA mice exhibited increased paracellular permeability and reduced protein synthesis in the colonic mucosa (L'Huillier et al, 2019 ). Oral glutamine supplementation restored colonic paracellular permeability and protein synthesis and increased the mucin-2 mRNA level without affecting body weight (L'Huillier et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy between dietary impact on intestinal permeability and gut barrier components is already documented in the literature 32 while these terms are often used interchangeably. We have previously shown that dietary supplementation by l -Glutamine was able to restore intestinal permeability without changing occludin mRNA levels in mice with activity-based anorexia 33 . We hypothesized that this vulnerability may be the result of microbiota changes.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is the most abundant amino acid in human blood, skeletal muscle, and the free amino acid pool [196]. At the intestinal level, it promotes enterocyte proliferation, regulates tight junction proteins [197], improves intestinal barrier function and reduces intestinal inflammatory response [198]. Glutamine is widely used in sports nutrition; in particular, its supplementation seems to increase muscle glycogen synthesis, reduce ammonia accumulation induced by exercise, and attenuate markers of muscle damage [199].…”
Section: Glutaminementioning
confidence: 99%